Community Attitudes toward Breastfeeding in Public Places among Western Australia Adults, 1995-2009. (May 2013) - Meng, Xingqiong; Daly, Alison; Pollard, Christina Mary; Binns, Colin William
Background: Community attitudes toward breastfeeding in public influence how comfortable women feel about continuing breastfeeding. Knowledge of the social context helps target breastfeeding-promoting interventions. Objective: To examine trends in Western Australian adult attitudes toward breastfeeding in public places. Methods: As part of 5 cross-sectional surveys from the Western Australian Nutrition Monitor Survey Series conducted between 1995 and 2009, 5496 adults aged 18 to 64 years were asked whether it was acceptable for mothers to breastfeed their babies in public places, including shopping centers, workplaces, and restaurants, and on public transport. Descriptive statistics and multinomial regressions were used to describe factors associated with attitudes toward publicly breastfeeding. Results: There was no change in the acceptance of breastfeeding in shopping centers, restaurants, and workplaces and on public transport over time, but in 2009, significantly fewer people said that it was unacceptable to breastfeed in public compared with 1995. Women, people older than 44 years, those born outside Australia, and the less educated were those most likely to say that breastfeeding in public was unacceptable. In the years that the question was asked, more than 97% of respondents said that breastfeeding was acceptable if a separate room was provided. Conclusions: Making breastfeeding acceptable and pleasant for mothers in public spaces is a key policy recommendation. Women, people older than 44 years, and those born outside Australia were most likely to respond that breastfeeding in public was unacceptable unless a room was provided. Given that, on average, 70% of the population said that breastfeeding in public was acceptable, investigation into why some women do not think so is warranted.